1989
DOI: 10.1002/clc.4960121106
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pain threshold in patients with effort‐induced angina pectoris and asymptomatic myocardial ischemia during exercise test

Abstract: Summary:The purpose of the present study was to analyze the prevalence of asymptomatic (silent) myocardial ischemia during exercise testing among patients with effort-induced angina pectoris, and further, to compare the pain threshold of patients with symptomatic and asymptomatic myocardial ischemia. A group of 26 patients comprised the study. In half of the patients myocardial ischemia during the exercise testing was silent and in one half it was symptomatic. Asymptomatic myocardial ischemia was defined as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…There are no consistent differences in the severity or duration of myocardial ischemia between silent and symptomatic episodes (6)(7)(8). There are, however, generalized differences in pain threshold and tolerance between individuals with predominantly silent versus predominantly symptomatic ischemia (9)(10)(11)(12). These differences may be associated with underlying variation in endogenous opioid activity, but other central nervous system (CNS) factors are probably involved as well (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There are no consistent differences in the severity or duration of myocardial ischemia between silent and symptomatic episodes (6)(7)(8). There are, however, generalized differences in pain threshold and tolerance between individuals with predominantly silent versus predominantly symptomatic ischemia (9)(10)(11)(12). These differences may be associated with underlying variation in endogenous opioid activity, but other central nervous system (CNS) factors are probably involved as well (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 86%
“…Some symptomatic patients tend to complain of chest pain early in the course of ischemic episodes, even if their symptoms are relatively mild, whereas others endure prolonged ischemia before reporting any symptoms (12,31). The relationship between delayed reporting and nonreporting (i.e., silent ischemia) has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have been reported to illustrate difference of pain thresholds between on some pain tests in silent MI and symptomatic MI (2,3). However, few was to be reported about whether the different analgesic could have various influence to pain threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,patients with silent ischemia showed decreased sensitivity to electrical pain, ischemic arm pain, and cold pressor pain (Droste & Roskamm, 1983). These results have been replicated by others (Droste, Meyer Blankenburg, Greenlee, & Roskamm, 1988;Pedersen, Pietersen, Madsen, Ballegaard, Meyer, & Trojaborg, 1989); however, one study reported no differences in pain perception in silent versus symptomatic ischemics (Glusman, Coromilas, Clark,Janal, Blood, KuW, & Burns, 1996). The patients with silent ischemia had significandy higher pain thresholds than symptomatic ischemics.…”
Section: Pain Perception In Coronary Artery Disease and Other Cardiacmentioning
confidence: 74%